Caracterización clínica y epidemiológica de pacientes con Covid-19 atendidos en Servicio de Emergencia del Hospital Clínico Universidad de Chile entre marzo y mayo 2020 - Soto R, Nicole; Cortés M, César; Muñoz P., Mariela; Postigo V., Javiera; Suquilanda J., Ana; Mellado T., Nelson; Rojas C., Antonio (Revista Hospital Clínico Universidad de Chile, 2020)
In December 2019, a novel coronavirus (SARS-CoV-2) emerged in China and has spread globally, creating a pandemic. The objective of this is study is to determinate clinical and epidemiological characteristics of patients with coronavirus en emergency department. The HCUCH Emergency Service treated a total of 6959 patients between March 13th and May 31th, of whom 1.278 were positive and had confirmed with coronavirus. The male sex was the most prevalent (59.7%). The most frequent symptoms in both groups were cough, myalgia and fever. In the group of ambulatory patients, headache stood out in 50% and in hospitalized patients, dyspnea with 67%. The mortality rate in hospitalized patients was 15.6%. Of these, 66.6% were older than 65 years. Regarding diagnosis of hospital discharge, 87.5% correspond to pneumonia. There is a higher prevalence of coronavirus disease in male patients. The most frequent comorbidities in hospitalized patients were HT and DM2. The highest rate of hospitalization and case fatality in people over 65 years of age. This information helps to characterize the profile of patients at risk in which prevention efforts should be focused.